2021
DOI: 10.1051/radiopro/2021025
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of standard ceiling-mounted surface guided radiotherapy systems for breast treatments on Halcyon™

Abstract: The present work investigates the benefits and challenges of applying surface guided radiation therapy (SGRT) to breast cancer treatments on the Halcyon™ (Varian, USA). Inter-fraction setup accuracy and treatment time were assessed by comparing CBCT shifts registered following SGRT-based vs. standard tattoo-based patient setup in two randomly selected groups of ten breast patients. Next, using a torso phantom and a volunteer, intra-fraction motion tracking accuracy and surface coverage were assessed for 3 adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
0
21
1
1
Order By: Relevance
“…Nguyen et al reported that SGRT signi cantly reduced setup errors compared with tattoos in all translational directions in patients with breast cancer [14]. They also showed that additional information acquired by the SGRT system can improve the positioning accuracy of breast cancer patients compared with the laser-based setup [14]. However, our study showed that only the average residual translational error in the vertical direction decreased signi cantly, but increased in the longitudinal direction.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Nguyen et al reported that SGRT signi cantly reduced setup errors compared with tattoos in all translational directions in patients with breast cancer [14]. They also showed that additional information acquired by the SGRT system can improve the positioning accuracy of breast cancer patients compared with the laser-based setup [14]. However, our study showed that only the average residual translational error in the vertical direction decreased signi cantly, but increased in the longitudinal direction.…”
Section: Discussioncontrasting
confidence: 60%
“…Because it is probably a comparison for the cranial region that are not affected by respiration in their study, which could be predominantly affected by chest wall motion caused by respiratory in our study. Nguyen et al reported that SGRT signi cantly reduced setup errors compared with tattoos in all translational directions in patients with breast cancer [14]. They also showed that additional information acquired by the SGRT system can improve the positioning accuracy of breast cancer patients compared with the laser-based setup [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, recent O-ring type linear accelerators such as the Halcyon™ (Varian Medical Systems, Palo Alto, USA) offer fast imaging times (within 17 s) compatible with a single BH and a wide-enough FOV (a longitudinal scan range of 24.5 cm) to allow for the validation of target and OAR positioning in DIBH. While standard SGRT systems cannot track intra-fractional surface motion inside the bore even with adjusted central camera positioning [22] , we used and evaluated here the new AlignRT InBore™ solution dedicated for closed-bore linacs [23] .…”
Section: Introductionmentioning
confidence: 99%